A Causal Relationship Model of Acceptance and Usage of Smartphone Educational Service Information System (SESIS) of Higher Education in Bangkok - Sobhanabhorn, Kiatikhorn; Bootthaisong, Suriya (วารสารวิทยบริการ มหาวิทยาลัยสงขลานครินทร์ | Academic Services Journal, Prince of Songkla University; Vol 28 No 3 (2560): Academic Services Journal, Prince of Songkla University, 2017)
The purposes of this research were to develop and validate a causal relationship model of acceptance and usage of smartphone educational service information system (SESIS) of higher education in Bangkok. The research model consisted of six latent variables: context, trust, personal initiative and characters, perceived usefulness, perceived ease of use, and intention to use. A sample of 382 undergraduate students in both private and government universities in Bangkok who had experiences of using SESIS participated in the study. The research instrument was a Five-point Likert scale. Data were analyzed by using SPSS Program and Mplus program version 6.12. The findings revealed that a causal relationship model of acceptance and usage of smartphone educational service information system (SESIS) of higher education in Bangkok with regard to the hypothesis was consistent to the empirical data. Trust had a positive direct effect on intention to use. Similarly, the perceived usefulness positively direct affected intention to use. In the contrast, personal initiative and characteristic, and perceived ease of use influenced the intention to use insignificantly. However, context significantly influenced the perceived usefulness and perceived ease of use, whereas perceived ease of use insignificantly affected the perceived usefulness. Finally, this research revealed that latent variable that affected the intention to use SESIS the most was trust. Hence, trust is the most important factor to consider in understanding information system acceptance and usage behavior. Keywords: smartphone educational service information system, intention to use, acceptance and usage of information technology, structure equation model